Studi Gastropoda Sebagai Bioakumulator Merkuri di Aliran Sungai Poboya Sulawesi Tengah - Miswan Miswan; Elijonnahdi Elijonnahdi; Mohamad Iqbal (Biology Department, Mathematics and natural science, Tadulako University, 2012)
The research to measure of mercury accumulated mercury at spesies Gastropods, (fresh water sanils) in Poboya stream have been conducted from March to May 2012. Snail were collected by “Hands Picking” technique at 4 station with Purpose Random that were based on population density. Snails were became to analysis Lymneae rubiginosa M that founded at station 1,2, and 3., Melanoides torulosa B and Melanoides tuberculatus L that founded at station 4. The result of mesuare of mercury accumulated showed that it’s station and kind snails spesies in station 4 were different. The high consentration found at Melanoides torulosa B in station 4 were 0,09 ppm, and then followed by Melanoides tuberculatus L. in station 4 were 0,06 ppm, Lymneae rubiginosa in station 3 and 1were 0,05 ppm, and the low consentation mercury at Lymneae rubiginosa M. in station 2 were 0,02 ppm. Key words: Gastropods, bioaccumulator, Merkury, Poboya stream